PENGARUH LEARNING CLIMATE TERHADAP JOB PERFORMANCE MELALUI CAREER RELATED CONTINUOUS LEARNING - Sarfilianty Anggiani (Universitas Trisakti, 2013)
This research objective is to identify and to analyze the relatioship of Learning climatehas an influence on Job Performance through the Career Related Continuous Learning. The result of the study showed that Learning climate influenced Job Performance through the career related continuous learning. Managerial implication and the recommendation for future study are provided.Keywords : Learning climate, Job performance, Career related continous learning